I Survived Hurricane Katrina, 2005 : I Survived # 3 - Tarshis, Lauren; Dawson, Scott (New York : Scholastic, 2011)
Barry's family tries to evacuate before Hurricane Katrina hits their home in New Orleans. But when Barry's little sister gets terribly sick, they're forced to stay home and wait out the storm. At first, Katrina doesn't seem to be as bad as predicted. But overnight the levees break, and Barry's world is literally torn apart. He's swept away by the floodwaters, away from his family. Can he survive the storm of the century -- alone?
007-010.
RL4.
Keywords: Hurricane Katrina, 2005 -- History -- Juvenile fiction; Hurricanes -- Juvenile fiction; Survival -- Juvenile fiction; Hurricane Katrina, 2005 -- Fiction; Floods -- Fiction; Survival -- Fiction; African Americans -- Fiction; Hurricane Katrina, 2005 -- Fiction; Floods -- Fiction; Survival skills -- Fiction; African Americans -- Fiction; New Orleans (La.) -- Fiction; New Orleans (La.) -- Fiction; Adventure fiction